Epidemiology of Hydatid Disease in Iraq: A Study of Hydatidosis Patients in Baghdad Province - Wasan Addai Al-Marsomy (Institute of Medico-legal Publications Pvt Ltd, 2021)
Cystic echinococcosis (CE) is a zoonotic disease worldwide caused mainly by the metacestode Echinococcusgranulosus. Hydatidosis disease is common in all countries of world, especially in the Middle East, inaddition to Asia, Africa and Europe. A person becomes infected with this disease through accidentalconsumption of water, soil or food contaminated with the faeces of infected dogs, which is the most commontype of method of infection. This parasite is transmitted to dogs when it ingests the infected organs of otheranimals that contain hydatid cysts. A study was conducted to study the infection rate between women andmen in Baghdad governorate. The results showed a highly significant increase in the incidence of infectionwith hydatid cyst among females (70.00%) in comparison to males (30.00%). The oldest age of hydatidosispatients was between 31-40 years (30.00%) with a significant differences between age groups and gender,while the lowest percentage was at age 41-50, in addition 51-60 age reached (10.00%). In regard to theprofession, the highest value of infection recorded in housewives (60.00%) and the lower percentages(6.67%) in the employees’ category. However, the most infection rate was within under primary educationlevel (40.00%), while the lowest percentage was at university education level (3.33%). The incidence ofliver infection (100%) is higher than the other organs, Moreover, it is the only affected organ that contains alarge number of hydatid cysts, Compared with lung, kidneys and spleen, which each recorded only two cystfor each of these affected organs in hydatid cyst patients, which was represented by significant differencesat (P<0.01) and (P<0.05).